Netze - Ein Überblick über Methoden ihrer strukturellen Erschließung in der Geographie - Leusmann, Christoph (ERDKUNDE, 1974)
Basic to the discussion is the presentation of given geographically relevant networks as planar graphs. This method is intended to enable networks and their elements to be described by indices. In addition, it allows the comparison of different networks and the handling of binary matrices in their significance for recognising structures. The question is, specifically, not about questions of 'usability' in the sense of an 'applied' geography but only an introductory review of the most important known methods of quantitatively describing such network structures.